Pencegahan Stunting Melalui Upaya 1000 Hari Pertama Kehidupan Dan Peningkatan Kemandirian Keluarga Di Desa Pilolaheya - Faramita Hiola; Nanang Roswita Paramata; Putri Ayuningtias Mahdang (Universitas Negeri Gorontalo, 2024)
One of the health problems for toddlers that is relatively high in various regions in Indonesia is stunting. Nutrition Study reached 2021 prevalence of stunting in Indonesia was 24.4%. Stunting is a growth and development disorder in the form of chronic malnutrition during a period of growth and development from the beginning of life. Pilolaheya Village is one of the loci for stunting in Bone Bolango Regency. This service aims to provide socialization on the incidence of stunting in Pilolaheya Village. After determining the child's nutritional status, education is carried out in the form of socialization on stunting prevention for pregnant women and mothers with toddlers using lecture and discussion methods and demonstrations of making healthy MPASI using local food ingredients, procurement of billboards as a health promotion tool regarding ODF (Open Defecation Free). The results show that there are still 13 toddlers at risk of stunting. In addition to nutritional factors, environmental health was closely related to the incidence of stunting. In Pilolaheya Village, most people still defecate in the river, as can be seen from the fact that there are still 50 houses that do not have a toilet. Another condition was the habit of the head of the family smoking in any place was dangerous for pregnant women and toddlers. This activity can help provide information and education to the public regarding the importance of the first 1000 days of life for children and increase awareness of the Pilolaheya community about the importance of maintaining a healthy environment to prevent the spread of disease.